Impact of the PD-1/PD-L1 inhibitor SCL-1 on MDA-MB231 tumor growth in a humanized MHC-double knockout NOG mouse model - Tomoatsu Ikeya; Tadashi Ashizawa; Akari Kanematsu; Chie Maeda; Akira Iizuka; Kazue Yamashita; Haruo Miyata; Yasufumi Kikuchi; Kouji Maruyama; Mamoru Ito; Ken Yamaguchi; Yasuto Akiyama (Scientific Reports)
Abstract Although triple-negative breast cancers are still challenging to treat, the development of novel neoadjuvant chemotherapy combined with immune checkpoint antibodies is promising. Our group developed the small compound-based anti-PD-1/PD-L1 inhibitor SCL-1 and reported its potent anti-tumor effects on various syngeneic mouse tumors. We herein investigated the efficacy of SCL-1 using an in vivo humanized NOG mouse system. We established a humanized mouse system using double major histocompatibility complex-knockout NOG mice transplanted with MDA-MB231 breast cancer cells and HLA-matched human PBMCs. Tumor-infiltrating lymphocytes (TILs) were analyzed using flow cytometry and real-time PCR. An RNA-sequencing analysis (RNA-seq) of SCL-1-treated MDA-MB231 tumors was performed to identify differentially expressed genes. Orally administered SCL-1 exerted potent anti-tumor effects with > 50% reduction in tumor sizes, which were dependent on PD-L1 expression and T-cell infiltration. Its effects were significantly stronger than those of nivolumab or atezolizumab. A TIL analysis revealed effector CD8+ T cells expressing cytotoxic markers and exhausted markers as well as increases in NK cells and B cells. RNA-seq showed the up-regulated expression of tumor-specific long non-coding (lnc) RNAs in SCL-1-treated tumor tissues, some of which exhibited high HLA-binding activity. SCL-1 exerted strong tumor growth inhibitory effects that were mediated by effector T-cell induction inside tumors and the up-regulated expression of lncRNAs as neoantigens leading to CTL activation. The up-regulated expression of lncRNAs in SCL-1-treated MDA-MB231 tumors is a novel result and may be one of the mechanisms responsible for the anti-tumor efficacy of SCL-1.